FRI0270 Tocilizumab Compared to Anti-TNFα Agents in Refractory Aortitis. (9th June 2015) - Palmou-Fontana, N.; Loricera, J.; Blanco, R.; Hernández, J.L.; Castañeda, S.; Ortego, N.; Peirό, E.; Collado, P.; Melchor, S.; Mera, A.; Pérez-Pampín, E.; Rubio, E.; et al.
Abstract : Background: Aortitis is often refractory to conventional immunosuppressive (IS) therapy. The use of biological therapy, such as tocilizumab (TCZ) and anti-TNFα agents, had been reported. Objectives: Our aim was to compare the efficacy of TCZ with anti-TNFα therapy in patients with aortitis. Methods: Retrospective multicenter study of patients with aortitis refractory to traditional IS agents. Results: We studied 44 patients (36 W/8 M; 51±19 years); 25 with TCZ and 19 with anti-TNFα agents (IFX=14, ADA=3, and ETN=2). Baseline features of patients on TCZ compared to the antiTNFα group (always in this order) showed a) mean age: 58±20 vs 42±13 years (p=0.003), b) women: 84% vs 79%, (p=0.97), c) underlying conditions: Takayasu arteritis, 8 vs 11 cases (p=0.08); giant cell arteritis, 15 vs 2 (p=0.0025); relapsing polychondritis, 1 vs 1 (p=0.59); ulcerative colitis, 0 vs 1 (p=0.88); Crohn's disease, 0 vs 1 (p=0.88); Behçet's disease, 0 vs 1 (p=0.88); sarcoidosis, 0 vs 1 (p=0.88); psoriatic arthritis, 0 vs 1 (p=0.88); and idiopathic aortitis, 1 vs 0 (p=0.88) d) mean of previous traditional IS agents (1.1 vs 1.7, p=0.069) and biological therapies (0.3 vs 0.1, p=0.23). After 3 months of treatment, most patients in both groups had experienced a clinical and acute phase reactants improvement, as well as a reduction of the corticosteroid dose. This favorable response was maintained over time (Table ). The improvement observed by imaging techniques was similar in both groups. After a median follow-up of 12 [9-17] vs 16 [12-36] months (p=0.014), TCZ was withdrawn due to severe neutropenia (n=1); recurrent pneumonia (n=1); cytomegalovirus infection (n=1) and systemic lupus erythematosus (n=1). Other adverse effects were thrombocytopenia (n=1) and infusional hypotension (n=1). One patient died due to a stroke in the setting of an infective endocarditis, and another one discontinued TCZ because of inefficacy. In the anti-TNFα group, 3 patients on IFX discontinued due to inefficacy (n=1), recurrent pneumonia (n=1) and severe infusional reaction (n=1). Conclusions: Biological therapy appears effective and relatively safe in patients with aortitis refractory to traditional IS drugs. In this series, TCZ seems to be slightly more effective than antiTNFα agents. Disclosure of Interest: None declared